Assessing Future Water Allocation under Climate Variability and Land Management Change in an Agricultural Watershed. (28th September 2022) - Phung, Quang A.; Thompson, Allen L.; Baffaut, Claire; Costello, Christine; John Sadler, E.
ABSTRACT: Climate change and population growth are increasing demand for water, causing water shortages across the United States. Decision makers need to understand the impact of climate on water allocation, particularly for watersheds with agricultural activity. The Missouri Salt River Basin (SRB) was selected for this study due to its soil characteristics, agriculturally dominated land use, and because it contains a major reservoir, Mark Twain Lake (MTL), which is the regional source of drinking water. The goal was to evaluate future water allocation in the SRB given projections of future climate and changing land management practices. Future climate data were input to the Soil and Water Assessment Tool, from which discharge outputs to MTL were entered in the Water Evaluation and Planning model to evaluate 2020–2059 crop and drinking water shortages. Water allocation strategies identified potential conflicts among users through scenario‐based approaches. The difference between water demand and supply was projected to increase by 100% because of climate change, from 3 to 6 million m 3 . Under a dramatic scenario, where irrigated land quadrupled, water shortage could be up to 38.5 million m 3 (1, 200% increase). Water withdrawals from the MTL may help alleviate part of the projected shortage; however, on‐farm pond storage would likely be more practical and cost‐effective. Overall, the paper provides a methodology for water allocation strategy.